Growthing Juniperus virginiana L. features in the conditions of the Carpathia - Pohribnyi, O. O.; Pohribna, L. S.; Zayachuk, V. Ya. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
Peculiarities of the introduction of plants in Kosiv region were studied. The types of diversity of the Arboretum of the Starokutsky PNDV of the NNP "Hutsulshchyna" have been determined. The course of growth of virginian juniper (Juniperus virginiana L.) in the conditions of Carpathia was analyzed.